Novel fluorescent organometallic materials - Woo, Chiat Tagg (University of Otago, 2011)
This thesis describes the synthesis and properties of some extended donor-acceptor dyads with the donor being a ferrocenyl moiety and a fluorescent naphthalimide group as the acceptor. Two series of extended ferrocenyl-naphthalimide dyads were prepared in reasonable yield depending on the synthetic route.